Transcending Binaries through Self-empowerment and Personal Development - Qazi Sarah Rasheed (South Asia Multidisciplinary Academic Journal)
Instead of zeroing in on the challenges that women in general, and Muslim women in particular, are expected to pose to structures of male authority, this article makes the point that Muslim women’s lives are not reducible to Islam or religion-based personal laws alone, and that circumstances impact their experiences of marriage and life after divorce. Without framing the actions of Muslim women within the logic of repression and resistance, this ethnographic study explores their transformative role in Muslim communities, and in a wider polity. It explores various strategies adopted by Muslim women activists vis-a-vis the global Islamic feminist movement while navigating their life courses. The strategies include: staging alternative, gender-neutral interpretations of Islamic scriptures; promoting reading of the Qur´an in native languages; taking over roles as mediators to resolve marital/familial conflicts; empowering women through education and awareness; and involving them in income-generating activities, often with state support.